CORNEAL CROSS-LINKING AS A THERAPEUTIC APPROACH IN PEDIATRIC KERATOCONUS (CIPEEX, 2025)
INTRODUCTION: Keratoconus is a disease characterized by progressive, asymmetric, and bilateral thinning of the cornea, resulting in irregular astigmatism and visual loss. It occurs mainly in childhood and adolescence and may progress until the fourth decade of life. The earlier the diagnosis, the faster and more aggressively the disease tends to progress, potentially causing significant visual impairment. Traditionally, management includes glasses or contact lenses, but these methods do not prevent the progression of keratoconus, which may eventually require corneal transplantation. Thus, corneal cross-linking (CXL) has emerged as a technique to stabilize the disease. CXL consists of applying riboflavin (vitamin B2) to the cornea, followed by exposure to ultraviolet-A (UV-A) light, promoting cross-link formation between collagen fibers, which increases corneal stiffness and helps prevent keratoconus progression. OBJECTIVE: To evaluate the effectiveness of CXL in preventing the worsening of keratoconus in children affected by the disease. METHODOLOGY: This is a literature review including four clinical trials retrieved from the PubMed database (2020–2025), in Portuguese and English. Studies addressing CXL in children with keratoconus and reporting outcomes regarding treatment effectiveness were included, while reviews and articles not covering the topic were excluded. RESULTS: The studies analyzed on CXL in pediatric keratoconus report consistent results regarding the effectiveness and safety of the procedure. In the short and medium term, most studies observed stabilization of corneal degeneration, along with improved visual acuity and maintenance or reduction of corneal curvature. In long-term follow-up, the benefits of treatment tended to persist, with good preservation of corneal integrity and visual acuity. Nevertheless, a small proportion of patients showed recurrence of disease progression, suggesting that the effect of CXL may not be definitive in all cases. Overall, the studies converge in indicating that cross-linking is a safe method, with a low incidence of significant complications and strong potential to preserve vision in children and adolescents with progressive keratoconus. Furthermore, the treatment was generally well tolerated, with few adverse events or severe complications. CONCLUSION: Therefore, CXL has proven to be an effective and safe alternative in the treatment of pediatric keratoconus, helping to stabilize or delay disease progression. Findings also suggest that early treatment may be crucial to avoid progression to advanced stages and reduce the need for corneal transplantation. Thus, cross-linking can be considered an essential tool in the management of keratoconus, offering promising outcomes in pediatric patients. Since the disease tends to be more aggressive in this age group, CXL contributes to preserving visual acuity and quality of life while preventing more severe cases.
Keywords: Therapeutics; Keratoconus; Child Health; Corneal Cross-Linking